Neural correlates of local contextual processing across stimulus modalities and patient populations. (May 2015) - Fogelson, Noa
Highlights: Behavioral and electrophysiological measures of local contextual processing. Facilitation of target detection utilizing predictive contextual information. Measures are comparable across stimulus modalities. Measures are altered across different neurological and psychiatric disorders. Potential biomarkers for frontal cognitive deficits. Abstract: The objective of the current review is to integrate information from a series of studies, employing a paradigm that evaluates local contextual processing using electrophysiological measures. Collectively these studies provide an overview of how utilization of predictive context changes as a function of stimulus modality and across different patient populations, as well as the networks that may be critical for this function. The following aspects of local contextual processing will be discussed and reviewed: (i) the correlates associated with contextual processing that have been identified in healthy adults, (ii) stimulus modality effects, (iii) specific alterations and deficits of local contextual processing in aging and across different neurological and psychiatric patient populations, including patients with prefrontal cortex lesions, Parkinson's disease, schizophrenia, and major depressive disorder, (iv) the potential for utilizing the correlates of local context as biomarkers for frontal cognitive dysfunction and (v) the role of frontal networks in the processing of contextual information. Overall findings show that behavioral and neural correlates associated with processing of local context are comparable across stimulus modalities, but show specific alterations in aging and across different neurological and psychiatric disorders.